Numerical simulation of the effects of downwash airflow and crosswinds on the spray performance of quad-rotor agricultural UAVs - Qiwei Guo; Yaozong Zhu; Yu Tang; Chaojun Hou; Mingwei Fang; Xiaobing Chen (Smart Agricultural Technology)
To elucidate the influence of rotor downwash airflow on droplet dynamics during agricultural UAV spraying, this study established a three-dimensional gas-liquid coupling numerical model. The synergistic effects of flight speed (1–5 m/s), operation altitude (2–4 m), and crosswinds (0–2 m/s) on droplet deposition and drift were systematically analyzed. Results demonstrated that increased UAV flight speed significantly tilted the downwash airflow backward, exacerbating drift losses for smaller droplets. Higher operation altitudes prolonged droplet residence times within airflow, further elevating drift risk. Crosswind velocity positively correlated with downwash airflow deflection angles, expanding airflow coverage under crosswinds; however, increasing crosswind velocities unexpectedly reduced droplet deflection angles. Experimental validation revealed a relative error between simulated and measured deposition of 27.2 % to 30 %, confirming the model's reliability. This study uniquely uncovers droplet drift patterns under crosswind conditions, offering new theoretical insights for optimizing UAV spray operations.